Assessment of periodontal health and necessity of dental treatment in the institutionalized elderly population of East Godavari district, Andhra Pradesh - Shaik K Sha; Ayub Khan; Karteek Eswara; Deepa Lakshmi Parchuri Venkata Suvarna; Karthik Kannaiyan; Nagarjuna Pottem (Wolters Kluwer Medknow Publications, 2019)
Aim: To assess the periodontal health condition and treatment needs among elderly people aged 60-85 years residing as inmates in the eight old age homes in East Godavari district, Andhra Pradesh, India. Settings and Design: A cross-sectional descriptive study was conducted to verify the oral health condition and treatment needs among elderly people aged 60-85 years. Materials and Methods: Modified World Health Organization (WHO) 2013 oral health assessment pro forma for adults was used to assess the oral health status and treatment needs, the clinical assessment of oral mucosa, loss of attachment (LOA) , community periodontal index, dentition status, and treatment need. Prosthetic status and prosthetic needs and related oral health information were obtained from WHO Oral Health Assessment Questionnaire. Statistical Analysis Used: SPSS 23 was used for statistical analysis. Chi-square test was used for age- and gender-wise comparison. P < 0.05 was considered statistically significant. Results: Among the study subjects aged 60-74 years, there were 28.1% males and 25.9% females, and in 75-85 years, 30.6% were males 15.3% were females. In terms of periodontal status (pocket scores), 66.2% of elderly people have pocket scores 6mm or more and presence of gingival bleeding in 75.9% of study subjects. Almost 24.4% had LOA scores of 12mm or more. Comparison of LOA scores based on age and gender was statistically significant (P < 0.001). Of the study participants, 50.3% need prompt treatment (including scaling). Almost more than half of the study participants require one or multiunit prosthesis as only 10.93% of elderly population has ≥20 or more natural teeth present. Conclusion: The study showed poor periodontal health among institutionalized elderly inmates. Oral mucosal lesions were found to be higher and oral health status was very deprived among the study population.